Vox ex Machina: A Cultural History of Talking Machines - Bell, Sarah A (The MIT Press, 2024)
How today's digital devices got their voices, and how we learned to listen to them.From early robots to toys like the iconic Speak & Spell to Apple's Siri, Vox ex Machina tells the fascinating story of how scientists and engineers developed voices for machines during the twentieth century. Sarah Bell chronicles the development of voice synthesis from buzzy electrical current and circuitry in analog components to the robotic sounds of early digital signal processing to today's human sounding applications. Along the way, Bell also shows how the public responded to these technologies and asks whether talking machines are even good for us. Using a wide range of intriguing examples, Vox ex Machina is embedded in a wider story about people—describing responses to voice synthesis technologies that often challenged prevailing ideas about computation and automation promoted by boosters of the Information Age. Bell helps explain why voice technologies came to sound and to operate in the way they do—influenced as they were by a combination of technical assumptions and limitations, the choices of the corporations that deploy them, and the habits that consumers developed over time.A beautifully written book that will appeal to anyone with a healthy skepticism toward Silicon Valley, Vox ex Machina is an important and timely contribution to our cultural histories of information, computing, and media.